Distinguishing persistent from occasional innovators: The case of Polish manufacturing firms - Anna Wziątek-Kubiak; Marek Pęczkowski (Center for Social and Economic Research (CASE), 2010)
This paper uses obstacles to innovation to investigate the heterogeneity of Polish innovating firms. Based on the frequency with which they introduce innovations, and using data from both CIS4 (for 2002-2004) and CIS5 (2004-2006), the paper distinguishes between two groups of innovating firms: those which introduced innovation in both periods covered by both CIS (called persistent innovators) and those which introduced innovation either in CIS4 or CIS5 (occasional innovators). Two steps analysis covering probit and biprobit models is introduced. The paper shows there is a discrepancy between the number of actual obstacles to innovation faced by firms and the number of obstacles perceived by managers of firms (subjective obstacles). It argues that the impact of obstacles to innovation on the innovation activities of occasional innovators differs from that of persistent ones. Obstacles to innovation reveal weaknesses in the innovation activities of persistent innovators. In the case of occasional innovators, some obstacles prevent firms from introducing innovation. The paper supports the view that the way firms innovate and the frequency with which they use knowledge resources is linked to the obstacles to innovation they face and their impact on innovation activities.
Keywords: O31; O33; D21; O52; 330; Innovation of the firms; Obstacles to innovation; Innovation sources; New Member States; Innovation; Innovationsmanagement; Industrie; Polen